Conservation of T cell epitopes between seasonal influenza viruses and the novel influenza A H7N9 virus - Mao, Huawei (Virol Sin, 2014)
A novel avian influenza A (H7N9) virus recently emerged in the Yangtze River delta and caused diseases, often severe, in over 130 people. This H7N9 virus appeared to infect humans with greater ease than previous avian influenza virus subtypes such as H5N1 and H9N2. While there are other potential explanations for this large number of human infections with an avian influenza virus, we investigated whether a lack of conserved T-cell epitopes between endemic H1N1 and H3N2 influenza viruses and the novel H7N9 virus contributes to this observation. Here we demonstrate that a number of T cell epitopes are conserved between endemic H1N1 and H3N2 viruses and H7N9 virus. Most of these conserved epitopes are from viral internal proteins. The extent of conservation between endemic human seasonal influenza and avian influenza H7N9 was comparable to that with the highly pathogenic avian influenza H5N1. Thus, the ease of inter-species transmission of H7N9 viruses (compared with avian H5N1 viruses) cannot be attributed to the lack of conservation of such T cell epitopes. On the contrary, our findings predict significant T-cell based cross-reactions in the human population to the novel H7N9 virus. Our findings also have implications for H7N9 virus vaccine design.